The Effect of 3-Post Drill Training on Two-Point Shooting Performance among Simfatic Basketball Club Athletes in Tulang Bawang - Putri Maharani; Lungit Wicaksono; Riyan Jaya Sumantri; Joan Siswoyo (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aimed to determine the effect of 3-Post Drill training on improving two-point shooting skills in basketball players. The research used a quasi-experimental method with a pretest–posttest control group design involving 20 players divided equally into experimental and control groups. The experimental group received 3-Post Drill training for six weeks, while the control group performed conventional training. The paired sample t-test showed a significant improvement in the experimental group (t = 20.146 > 2.262; p < 0.05) but not in the control group (t = 0.557 < 2.262; p > 0.05). The independent sample t-test on posttest scores indicated a significant difference between groups (t = 9.043 > 2.101; p = 0.000), confirming that the 3-Post Drill had a substantial effect on two-point shooting performance. The normalized gain value (g = 0.48) was categorized as moderate, highlighting the effectiveness of structured technical repetition from three shooting positions in enhancing shooting performance, coordination, and consistency.